Új tagállamok, új modell? - Farkas Beáta (Műhelytanulmányok, 2009)
In this paper the question is raised how the institutional system of the New Member States of the European Union fits to models elaborated and accepted for the Old Member States (Anglo-Saxon, Nordic, Continental, Mediterranean); whether it approaches to any of these or it forms a new model. Amable’s study was considered as a starting point as he underpinned the existence of the four models by statistical analyses. However, the database had to be built anew because the OECD database used by Amable did not contain data on some of the New Member States. Cyprus and Malta had to be omitted here as well. In our cluster analysis based on data from the middle of the first decade of the years 2000, almost the same clusters are outlined as in Amable’s investigation. The main difference between the two analyses is that, in our case, the Anglo-Saxon model seems to appear very weakened in the European Union. Concerning the New Member States, the cluster analysis shows that differences between the EU-15 and new Member States are much larger than differences within the group of New Member States. This way a new, fifth, Central and Eastern European model can be described. The peculiarities of the Central and Eastern European model can be basically explained by three factors: the lack of capital, the weakness of the civil society, and the impact of the European Union and international organizations. To evaluate the future of the Central and Eastern European model, Porter’s competitive development theory is applied. Taking into account the settled institutional system, it is to be expected that the present asymmetric interdependency becomes long-lasting. This may easily turn the Lisbon Strategy intending to develop the whole European integration into innovation driven economies into an illusion, even in the long run. At the end of the study, based on our findings, some ideas are formulated on the Hungarian economic policy.